Al-Sajā’ir wa shabakat al-‘ulamā’ al-Miṣrīyīn fī Nusantara: Dirāsah fī makhṭūṭ “Bāb fī bayan shurb al-dukhān” - Rohmana, Jajang A. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
This study reveals on fatwas concerning cigarettes in the Archipelago in the 19th century. The primary source is an Arabic manuscript from Kuningan, West Java, digitized by DREAMSEA, entitled “Bāb fī Bayān Ḥukm Shurb al-Dukhān”. It does not only use arguments from sharia, the interpretation of ulama, and health reasons but also refers to myths and conspiracies. This study finds that this manuscript mentions the existence of ḥaram (prohibited) and makrūh (not legally forbidden but discouraged) on cigarettes referring to two Egyptian ulama in the 17th century. Through analyzing fiqh and social history, this philological study discloses the connection between its author with the Egyptian’s ulama networks as a new center for ideas of Islamic civilization aside from Haramayn. Hence, the arguments of the manuscript openly consider many aspects of sharia in responding to such a new tradition (cigarettes) in the Muslim community. This is different from similar manuscripts discussing this kind of fatwa in the 19th century which only judge as haram so that it is considered politically as a form of a critique against the colonial tobacco business policies.